Seroprevalence of Hepatitis C Virus (HCV) in Southern Punjab (Medical Forum Monthly, 2024)
Objective: To find out the seroprevalence of Hepatitis C Virus (HCV) detected on blood screening in blood donors and candidates for recruitment in Armed forces of Pakistan from Southern Punjab.Study Design: Observational studyPlace and Duration of Study: This study was carried out in the Department of Pathology, Combined Military Hospital (CMH), Multan from January to December 2013.Materials and Methods: Serological blood screening of blood donors and candidates coming for recruitment in armed forces of Pakistan at CMH Multan was performed. Test was performed with rapid screening kit initially and suspected cases were confirmed with third generation ELISA technique. Bio-data of Hepatitis C virus (HCV) positive cases was collected, analyzed and compared with national and international literature. Results: A total of 10666 persons were screened out, 311 (2.91%) were HCV positive. Conclusion: Seroprevalence of HCV in this region is also high like rest of the world. Public awareness about the disease, blood screening before transfusion, use of disposable syringe, proper disposal of contaminated material and prevention from sexual transmission are required to decrease the incidence and its spread.